DIVERSITY OF BAT-ASSOCIATED LEPTOSPIRA IN THE PERUVIAN AMAZON INFERRED BY BAYESIAN PHYLOGENETIC ANALYSIS OF 16S RIBOSOMAL DNA SEQUENCES - MATTHIAS, MICHAEL A. (2005)
The role of bats as potential sources of transmission to humans or as maintenance hosts of leptospires is poorly understood. We quantified the prevalence of leptospiral colonization in bats in the Peruvian Amazon in the vicinity of Iquitos, an area of high biologic diversity. Of 589 analyzed bats, culture (3 of 589) and molecular evidence (20 of 589) of leptospiral colonization was found in the kidneys, yielding an overall colonization rate of 3.4%. Infection rates differed with habitat and location, and among different bat species. Bayesian analysis was used to infer phylogenic relationships of leptospiral 16S ribosomal DNA sequences. Tree topologies were consistent with groupings based on DNA-DNA hybridization studies. A diverse group of leptospires was found in peri-Iquitos bat populations including Leptospira interrogans (5 clones), L. kirschneri (1), L. borgpetersenii (4), L. fainei (1), and two previously undescribed leptospiral species (8). Although L. kirschenri and L. interrogans have been previously isolated from bats, this report is the first to describe L. borgpetersenii and L. fainei infection of bats. A wild animal reservoir of L. fainei has not been previously described. The detection in bats of the L. interrogans serovar Icterohemorrhagiae, a leptospire typically maintained by peridomestic rats, suggests a rodent-bat infection cycle. Bats in Iquitos maintain a genetically diverse group of leptospires. These results provide a solid basis for pursuing molecular epidemiologic studies of bat-associated Leptospira, a potentially new epidemiologic reservoir of transmission of leptospirosis to humans.